From Power to Sustainability? Unpacking the Role of Justice in Agricultural Commodity Supply Networks - Felipe Alexandre de Lima; Evelyne Vanpoucke; Stefan Gold; Stefan Seuring (Journal of Operations Management, 2025)
Agricultural commodity supply networks in the Global South are essential for securing the global supply of crops and livestock. However, they are challenged by power asymmetries, which cause injustice and jeopardize social equity, environmental stewardship, and economic viability for disadvantaged actors. To address this challenge, it is imperative to understand how power impacts justice and sustainability. To this end, we examined a supply network in Mato Grosso, Brazil, that faced power asymmetries through 49 semi-structured interviews, field observations, and archival data. The analysis unveiled three forms of power use—excessive, strategic, and balanced—and associated tactics, impacting justice and sustainability outcomes in various ways. We illustrate, for example, how excessive power manifested in traders' abusive tactics, who compelled farmers to accept quality discounts due to external factors, such as heavy rain or poor road conditions. In response to these injustices, farmers cascaded the pressure through the supply network, disproportionately affecting disadvantaged actors, for instance, by withholding rural workers' wages for low productivity or eradicating wildlife deemed detrimental to profitability. Based on these findings, we provide a set of six propositions and a theoretical model that elucidate how power can be leveraged to foster fairer and more sustainable agricultural commodity supply networks.
Keywords: 650; agricultural commodity; global south; justice; power tactics; supply network; sustainability